Meningkatkan Hasil Belajar Siswa Dengan Model Discovery Learning Materi Manusia Sebagai Citra Allah Kelas VII SMPN 1 Singkawang - Timotius Tomi (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
Students who were accepted at Singkawang 1 Public Middle School did not all comply with their main preferences causing low learning independence and learning achievement, so they did not reach KKTP, namely 75. This study aims to: 1) Know the increase in learning independence in human material as personal beings VII SMP Negeri 1 Singkawang . 2) Knowing the effectiveness of the Discovery Learning method in increasing student learning outcomes in the material I Am the Unique Image of God at Singkawang 1 Public Middle School. This study applies a quantitative descriptive approach, namely making descriptive of a situation objectively using numbers, starting from data collection, interpretation and display of the results. The research design is Classroom Action Research which is carried out in two. (2) cycle, to class VII students with a population of 6 people. The research results show that. (1) The Discovery Learning method can increase the independence of learning in the material of human beings being personal class VII of SMP Negeri 1 Singkawang.